An investigation into the use of IEEE 1394 for audio and control data distribution in music studio environments - Laubscher, Robert Alan (Rhodes University, Faculty of Science, Department of Computer Science, 1999)
This thesis investigates the feasibility of using a new digital interconnection technology, the IEEE-1394 High Performance Serial Bus, for audio and control data distribution in local and remote music recording studio environments. Current methods for connecting studio devices are described, and the need for a new digital interconnection technology explained. It is shown how this new interconnection technology and developing protocol standards make provision for multi-channel audio and control data distribution, routing, copyright protection, and device synchronisation. Feasibility is demonstrated by the implementation of a custom hardware and software solution. Remote music studio connectivity is considered, and the emerging standards and technologies for connecting future music studio utilising this new technology are discussed.,Microsoft Word,Adobe Acrobat 9.46 Paper Capture Plug-in
Keywords: Digital electronics; Sound -- Recording and reproducing -- Digital techniques; MIDI (Standard); Music -- Data processing; Computer sound processing